PVD coating as a possibility to increase the load capacity of gearings to scuffing - Bošanský, Miroslav; Kožuch, I.; Fedák, M. (НТУ "ХПІ", 2008)
In the article we describe the possibilities of increase of the contact load capacity of unhardened C-C toothed gear. The use of metal coatings proves to be one way. On the basis of a comparison of the individual methods of depositing the coating technology of PVD (physical vapour deposition) proves to be suitable application for the case of gearings. This technology is used for depositing the hard coatings. C-C toothed gear, coated with TiN, in interaction with ecological lubricant was experimentally verified with respect to scuffing on test stand by Niemann and compared to the hardened involvent gearing.

Стаття знайомить з можливостями підвищення контактної несучої здатності незагартованого опукло-ввігнутого зубчастого зачеплення. Однією з можливостей є використання металевих покрить. На підставі порівнювання окремих методів нанесення покриття підхожим виявляється у випадку зубчастих передач технологія PVD (physical vapor deposition). Ця технологія використовується для нанесення твердого покриття. TiN покрита С-С зубчаста передача у взаємодії з обраними екологічними мастилами була експериментально провірена проти заїдання на стенді Німанна/Niemann/ та порівнювалася з загартованою евольвентою зубчастою передачею.
Keywords: TiN coating; tooth gear; ecological lubricant; test stand by Niemann; chemical vapour deposition; CVD